How and when mindfulness inhibits emotional exhaustion: a moderated mediation model - Bayighomog, Steven W.; Ogunmokun, Oluwatobi A.; Ikhide, Juliet E.; Tanova, Cem; Anasori, Elham (Springer, 2023)
Clinical studies have suggested the importance of mindfulness in curbing psychological illbeing. However, this has been overlooked in the occupational setting, especially in some service sectors where employees are more prone to work-related stress and burnout. Therefore, the purpose of this study is to examine the indirect relationship between mindfulness and emotional exhaustion through psychological distress, and the moderating role of workplace bullying. Employees in the North Cyprus-based hospitality sector (Study 1) and in the Nigeria-based healthcare sector (Study 2) completed surveys during a time-lagged data collection procedure. The results of both studies indicated that mindfulness could significantly reduce psychological distress and subsequently emotional exhaustion when workplace bullying was low to moderate. The current work extends the extant mindfulness and occupational wellbeing literature by shedding more light on the underlying and conditional mechanisms explaining the salutary role of mindfulness on wellbeing. In the same vein, it also expands the burnout and workplace bullying body of knowledge that is particularly understudied in sub-Saharan Africa. Additional theoretical and practical implications of the findings are discussed further, alongside limitations and future studies directions.
Keywords: Mindfulness; Emotional exhaustion; Workplace bullying; Psychological distress; Occupational health; Wellbeing